Pengaruh Gaya Kepemimpinan Partisipatif dan Lingkungan Kerja Fisik Terhadap Semangat Kerja Karyawan - I Nyoman Partha Astinatria; I Wayan Gde Sarmawa (Widya Manajemen, 2020)
The purpose of this study was to determine the effect of leadership style and physical work environment on employee morale. This research was conducted at CV. Dinayu convection which is located at Jalan Patih Nambi no 99, Ubung Kaja, Denpasar Utara. The population and sample of the study were all employees in the CV. Dinayu, totaling 54 people. The data collection method uses a questionnaire that generally contains respondents' perceptions of participative leadership style, physical work environment, and employee morale. Data analysis was performed with multiple regression linear tests. The results of this study indicate that the leadership and work environment variables have a positive and significant effect on employee morale in the CV. Dinayu conjunction convection.